Efeito diferencial do diazepam sobre a atividade da enzima Na+,K+-ATPase no hipocampo e córtex entorrinal - Marafiga, Joseane Righes (2016)
Na+,K+-ATPase is ubiquitously expressed in the plasma membrane of all animal cells where serves as the principal regulator of intracellular ion homeostasis. Na+,K+-ATPase activity is activated by Na+ and K+ and current evidence indicates that total Na+,K+-ATPase activity is, in general, inhibited by anions. However, the effect of pharmacologically-induced Cl- flux on α1- and α2/3-subunit containing Na+,K+-ATPase activity is not established. In this study we investigated the effect of diazepam, a GABAA receptor positive allosteric modulator, on α1- and α2/3-subunit containing Na+,K+-ATPase activity. Hippocampal and cortical slices were incubated with diazepam (0, 0.05, 0.15 or 0.5 μM) and/or flumazenil (0, 0.005, 0.015, 0.05, 0.15, 0.5 or 1.5 μM) for 10 minutes. After incubation the slices were homogenized and α1 and α2/3 Na+,K+-ATPase activity were assayed using ouabain 3 μM (that inhibits α2/3-subunit containing Na+,K+-ATPase) and 4 mM (that inhibits both isoforms). Diazepam caused a 50% decrease of α2/3-subunit containing Na+,K+-ATPase activity in the hippocampus, but did not alter enzyme activity in the entorhinal cortex. The effect of diazepam was prevented by flumazenil, indicating that the decrease of Na+,K+-ATPase was involved GABAA receptors. Furthermore, a low chloride medium abolished the diazepam-induced decrease of Na+,K+-ATPase activity. Our data suggests that Na+,K+-ATPase in the hippocampus is sensitive to the pharmacological effects of a benzodiazepine by GABAA receptor-mediated mechanisms. Keywords: sodium pump. GABAA receptor. diazepam. flumazenil. chloride ion. hippocampus. entorhinal córtex.